STUDY ON THE SYNTHESIS OF MONOLAURIN AS ANTIBACTERIAL AGENT AGAINTS Staphylococcus aureus - Galuh Widiyarti; Muhammad Hanafi; Wahyudi Priyono Soewarso (Indonesian Journal of Chemistry, 2009)
The monolaurin compound had been synthesized from lauric acid and glycerol by using sulfuric acid (H2SO4) as catalyst. The synthesis of monolaurin was done by batch esterification on the free solvent system. The esterification reaction was performed on the equivalent mol ratio between lauric acid and glycerol 1:1, in the presence of 5% H2SO4, at 130 °C, for 6 hours, produced ester compounds on 59.29%. The products of column chromatography on silica gel purification are monolaurin and dilaurin in amount of 31.05 and 4.48%, respectively. The monolaurin and dilaurin were identified by TLC, FTIR, GC-MS, and NMR spectrometer. The spectral data of monolaurin was compared to spectral data of standard monolaurin. The result of NMR identifications showed that synthesis products were a-monolaurin and a,a'-dilaurin. The antibacterial activity of synthesis products was tested against Staphylococcus aureus. The activity result showed that the antibacterial activity of monolaurin is more active than dilaurin.